The 34S/32S isotopic ratio measured in the dust of comet 67P/Churyumov–Gerasimenko by Rosetta/COSIMA - J A Paquette; K Hornung; O J Stenzel; J. Rynö; J. Silen; J. Kissel; M. Hilchenbach; The Cosima Team (Oxford University Press, 2022)
The isotopic ratio 34S/32S has been measured in cometary gas for a few comets, but it has only been measured in cometary dust by stardust. The dust measurements find a value of the ratio that is consistent with the Vienna Canyon Diablo Troilite value of 0.0442 within errors, but there is more spread in the values from cometary gas. In this paper, we present the result of measurements of the sulphur isotopic ratio in dust from Comet 67P/Churyumov–Gerasimenko with the COSIMA instrument aboard the Rosetta spacecraft. We find a result of 0.0463 ± 0.0057, which is consistent within errors with the terrestrial value.